Evaluation of information services and needs for pregnant women, fathers and infants in China - Zhou, Qinqin (My University, 2024)
According to the statistics from the Ministry of Industry and Information Technology, as of June 2023, China's online population has reached 1.079 billion people, an increase of 11.09 million people compared to December 2022, with an internet penetration rate of 76.4%. With the rapid development of the big data era, users' dependence on the internet is increasing, not only bringing a substantial user base to the mobile internet market but also fostering the flourishing development of mobile applications. In the online environment, users engage in sharing experiences through posting and commenting on mobile applications (APPs) within online communities. This information holds significant value for exploring user needs and satisfaction. This study aims to combine content analysis of academic literature and text mining of APP forum comments to delve into the differences between information services provided by maternal and infant health-related APPs and the demands of users for maternal and child health information. It also aims to provide targeted improvement suggestions for health information services offered by maternal and child health-related mobile applications. The paper begins by summarizing the current research status of maternal and child health information demands and services both domestically and internationally, subsequently formulating research questions. It then dissects the categories of maternal and child health information demands using the research method of grounded theory. The study utilizes open coding, axial coding, and selective coding on collected online academic literature, forming a three-tier framework for maternal and child health information demands. Following this, text mining is employed to preprocess question-and-answer and comment texts obtained from APP online communities. The TF-IDF algorithm is applied to extract high-value feature words from comment texts, which are then subjected to clustering and frequency statistics. This process supplements the three-tier framework for maternal and child health information demands. Qualitative content analysis is conducted to manually code video and article content in the APP, extracting three-tier categories of information services. Lastly, by comparing and analyzing the categories of maternal and child health information demands with the categories of health information services extracted from the APP, differences between the two are identified. The paper concludes by offering reasonable suggestions for the development and operation of maternal and child health-related applications. The research findings demonstrate that maternal and child health information needs can be categorized into six main themes, 15 subcategories, and 68 tertiary categories. Maternal and child health information services comprise four categories, 15 subcategories, and 53 tertiary categories. There exists a notable disparity between maternal and child health information needs and services, particularly evident in prenatal examinations, fetal development, infant feeding and care, prenatal preparation, preconception knowledge and precautions, infant education, reproductive policies, and matters related to work and maternity leave. The study reveals the gap between information needs and services in the field of maternal and child health, pinpointing specific gaps in requirements during the prenatal, antenatal, and infancy stages, thereby offering targeted directions and focal points for improving maternal and child health services. Based on these research findings, this paper proposes recommendations for the development of high-quality information services for maternal and child health apps from two perspectives: the organization and implementation of software systems and the categories of information services. From the viewpoint of software system organization and implementation, it is suggested to enhance and optimize functional design, refine facet system design, and structure information needs. From the perspective of information service categories, it is recommended to establish a specialized preconception advice module, provide pregnancy health monitoring and knowledge dissemination, comprehensive infant feeding and care information, as well as policy and institutional guidelines. These recommendations aim to enhance the quality of maternal and child health apps by improving software functionality design and providing professional information service content, enabling users to conveniently access comprehensive and effective information tailored to preconception, pregnancy, and childcare stages, thereby fostering maternal and child health development.
Keywords: Maternal and Child Health, Information Demands, Information Services, Text Mining